2013
DOI: 10.1038/ijir.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response in patients with primary premature ejaculation

Abstract: To evaluate the possible role of the autonomic (sympathetic) nervous system function among the patients with primary premature ejaculation (PPE) and determine whether there is an etiological basis for this condition. We performed sympathetic skin response located in the penis (PSSR) in 52 patients with PPE and 46 normally potent men. The latencies and amplitudes of PSSR were measured. The PSSR waveforms were classified into P type and N type according to the waveform characteristics. The waveform distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 33 publications
5
52
0
1
Order By: Relevance
“…Additionally, the serum 5‐HT level in PE patients after 8‐week sertraline treatment increased significantly, accompanying with IELT prolonged [40]. More recently, our studies and other reports indicate that the sympathetic overactivity is another factor involved in the pathological mechanisms of PPE [9,10,41]. Therefore, the increased sympathetic input may facilitate the activation of the SGE in response to a minimal amount of external stimulation, and SSRI may delay ejaculation by enhancing the role of the descending inhibitory serotonergic projections from the brainstem to SGE [30], which is in agreement with the above second hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, the serum 5‐HT level in PE patients after 8‐week sertraline treatment increased significantly, accompanying with IELT prolonged [40]. More recently, our studies and other reports indicate that the sympathetic overactivity is another factor involved in the pathological mechanisms of PPE [9,10,41]. Therefore, the increased sympathetic input may facilitate the activation of the SGE in response to a minimal amount of external stimulation, and SSRI may delay ejaculation by enhancing the role of the descending inhibitory serotonergic projections from the brainstem to SGE [30], which is in agreement with the above second hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, PPE has been claimed to be caused by somatic disorders and/or neurobiological imbalances, such as penile hypersensitivity, hyperarousability, and genetic predisposition [6]. More recently, our study, in which sympathetic skin response located in the penis (PSSR) tests were used, indicated that hyperactivity of the sympathetic nervous system may be another factor involved in the pathological mechanisms of PPE [9]. The results are in agreement with a recent study reporting the sympathetic overactivity in PPE patients through measuring 24-hour heart rate variability (HRV) in the men with PPE [10].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The latency of the penile sympathetic skin response (PSSR) was significantly shorter and the amplitude of the PSSR was significantly larger in patients with lifelong PE compared with normally potent men. 10 Furthermore, the amplitude of PSSR in patients with lifelong PE was decreased and the latency of PSSR was prolonged after 8-week sertraline treatment. 11 Our previous study showed that patients with PE had higher amyloid precursor protein (APP) levels in seminal plasma compared with the control group.…”
Section: Introductionmentioning
confidence: 95%